Building without Burning: A Case Study and Guide for White Teachers Hoping to Teach about Race and Power. - Bonfiglio, Gabriela T. (Tufts Archival Research Center, 2018)
This thesis takes a course I taught through the Tufts Experimental College on counternarrative US history as a case study for how to teach about race and power, especially in the moment of Trump and Black Lives Matter, and as a white teacher.